1984
DOI: 10.1016/0165-0327(84)90050-8
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind clinical study comparing alprazolam and doxepin in primary unipolar depression

Abstract: The therapeutic effect and safety of alprazolam and doxepin were studied in 126 outpatients suffering from primary unipolar depression. The 6-week study was double-blind with a random allocation of treatment. Patients were treated with a flexible dose of 1.0-4.5 mg of alprazolam and 50-225 mg of doxepin per day. The mean final doses were 2.7 mg for alprazolam and 137.5 mg for doxepin. The results indicate that alprazolam and doxepin were equally efficacious. The incidence of side-effects was lower in the alpra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The dropout rate was significantly greater with TCA in 2 studies [46,51]; in Ansseau et al [53], it was significantly more common with diazepam than with amitriptyline due to ineffectiveness after 2 weeks. Adverse reactions, such as anticholinergic symptoms, were significantly more frequent with TCA in 5 studies [42,[44][45][46]53], but no differences were observed between TCA and BZD in 3 other reports [41,47,52].…”
Section: Systematic Review Of Rct On the Efficacy Of Bzd In The Treatmentioning
confidence: 95%
See 2 more Smart Citations
“…The dropout rate was significantly greater with TCA in 2 studies [46,51]; in Ansseau et al [53], it was significantly more common with diazepam than with amitriptyline due to ineffectiveness after 2 weeks. Adverse reactions, such as anticholinergic symptoms, were significantly more frequent with TCA in 5 studies [42,[44][45][46]53], but no differences were observed between TCA and BZD in 3 other reports [41,47,52].…”
Section: Systematic Review Of Rct On the Efficacy Of Bzd In The Treatmentioning
confidence: 95%
“…Participants were assigned at random to the conditions in all studies, and all were double-blind trials. ITT analyses were performed in 8 reports [19,20,23,28,30,31,42,53], completers' data only were reported in 12 studies [25,27,29,37,39,41,44,45,47,49,50,54], and handling of attrition was not reported in 2 studies [46,48].…”
Section: Meta-analysis On the Efficacy Of Bzd In The Treatment Of Depmentioning
confidence: 99%
See 1 more Smart Citation
“…First-line treatments in depression are tricyclic antidepressants (TCAs). Clinical studies in depressed patients showed that alprazolam is at least equally effective as TCAs, such as amitriptyline (13,66,76,126,157,249), imipramine (84,86,87,180,212,277), dosulepine (41), desipramine (85,210), or doxepin (9). However, other studies reported that, although alprazolam provided symptom relief, amitriptyline (124,159,227) and imipramine (103,161) were significantly more effective.…”
Section: Depressionmentioning
confidence: 99%
“…Nonetheless, re cently, alprazolam, a new triazobenzodiaze pine. was purported as effective as tradi tional antidepressants in major depressive disorders [133] or anxious depression [4], A benzodiazepine obviously would present po tentially less side effects than tricyclics. Thus, clinicians may be inclined to select alprazolam for the medically ill who suffers from a major depressive episode.…”
Section: The Use O F Antidepressant Drugsmentioning
confidence: 99%